Uptake of [68Ga]-NODAGA-E[(cRGDyK)]2 is related to improvement in pump function in rats with chronic ischemic cardiomyopathy treated with cell therapy. (14th October 2021) - Follin, B; Hoeeg, C; Nielsen, C H; Hunter, I; Bentsen, S; Jensen, J K; Binderup, T; Ekblond, A; Ripa, R S; Kastrup, J; Kjaer, A
Abstract: Background: An increasing number of patients living with chronic ischemic cardiomyopathy (ICM) are potential candidates for cell therapy, including adipose tissue-derived mesenchymal stromal cells (ASC). However, proper assessment of clinical effects in relation to cellular effector mechanisms, such as angiogenesis, is currently lacking. Purpose: To investigate the prognostic value of assessing angiogenesis non-invasively using novel PET imaging in terms of functional outcome after cell therapy in a homologous animal model of ICM. Methods: Myocardial infarction was induced by permanent ligation of the left anterior descending coronary artery. Four weeks after infarction, the rats were scanned with [18F]-FDG and echocardiography, and based on left ventricular ejection fraction (LVEF) and infarct size randomized to allogeneic ASC treatment (n=14) or saline (n=9). Animals were treated using echo-guided trans-thoracic intramyocardial injections. Follow-up echocardiography was performed four weeks after treatment. Angiogenesis was assessed non-invasively using the [68Ga]-NODAGA-E[(cRGDyK)]2 (RGD) PET-tracer before treatment and two weeks after the treatment (Figure). The output was RGD-uptake by maximum standardized uptake value (SUVmax). Results: RGD-uptake in the infarct area significantly decreased in the saline group (p=0.04), while this decline was not significant in the ASC group (p=0.58). There was no effect on LVEF of the cell therapy in this study (p=0.70). When the rats were grouped by RGD-uptake post treatment, the high RGD-uptake group (n=8) improved LVEF compared to the rats with medium or low RGD-uptake (n=15, p=0.04) irrespective of the treatment. This could indicate that non-invasive detection of a high degree of myocardial angiogenesis measured using RGD is predictive of improvement in cardiac pump function in ICM. Conclusions: Following injection of ASC or saline, a high RGD-uptake precluded improvement in pump function. This is the first evidence of how uptake of the novel RGD tracer relates to changes in pump function in ICM and the results could affect the design of future clinical trials using regenerative therapy for ICM patients. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): Aase and Ejnar Danielsens FondDoctor Sofus Carl Emil Friis and wife Olga Doris Friis' Scholarship